Investigation of a proton-conducting SOFC with internal autothermal reforming of methane - Patcharavorachot, Yaneeporn; Arpornwichanop, Amornchai (My University, 2012)
In this study, a proton-conducting SOFC (SOFC-H + ) with internal autothermal reforming of methane is proposed to overcome the carbon formation problem facing in the SOFC-H + with internal steam reforming. A one-dimensional steady-state model coupled with a detailed electrochemical model is developed to investigate the performance of the SOFC-H + (power density and fuel cell efficiency). The effect of key operating parameters such as temperature, H 2 O/CH 4 and O 2 /CH 4 feed ratios, on the SOFC-H + is also determined in this study. © 2012 Elsevier B.V.
Keywords: Autothermal reforming; Direct internal reforming; Methane; Proton-conducting SOFC